Assessing the Capital Efficiency of Healthcare Information Technologies Investments: An Econometric Perspective - Meyer, Rodolphe; Degoulet, Patrice (Yearbook of Medical Informatics, 2008)
Objectives To examine the different methods that can be used in the quantification of the added value of information technologies (IT) in the health care sector. This quantification represents a major issue for decision-makers and health care professionals when they have to plan an IT investment.MethodsArticles were chosen via Medline, internet and the University of Geneva bibliographic portal. Some of the papers were obtained directly from their authors. We examine the most current methods used to evaluate IT return on investment (ROI) in the general business and in the health care sector, drawing attention on methods traditionally used in macro economic studies that could reveal themselves disruptive for IT ROI impact evaluation in hospitals.Results Financial and accounting methods can provide interesting data on a specific IT project but are usually incomplete for revealing the global IT investment influence. Econometric methods tend to demonstrate the positive impact of health care IT (HIT) on hospital production and productivity. Hospitals having higher levels of IT investment tend to deliver a higher level of clinical quality and show improved hospital cost performances.Conclusions Information technologies are so intermingled with people and processes that the identification of specific IT benefit remains questionable. Using macro economic tools could be the best way to analyze and compute IT ROI in health care. Econometric tools take into account all types investments (inputs) and all the returns (outputs) enabling the precise measurement of IT investments impact, breakeven points, and possible threshold levels, thus providing helpful intelligence to reach the higher levels of IT governance in hospitals.
Keywords: Econometrics; return on investment (ROI); health care information technologies; HIT; production function; Cobb-Douglass; productivity